Pengaruh Kecerdasan Emosional, Komunikasi Interpersonal, Komitmen Organisasi terhadap Manajemen Stres Kerja - Hutagalung, Inge (Interaksi: Jurnal Ilmu Komunikasi, 2014)
Stress in the workplace is not a new phenomenon. Effective stress management at work makes employees capable of controling themselves in work environment so they will accept potential problems as challenge and not as threat. The research results indicate that emotional quotient and interpersonal communication have close influence to stress management. Moreover, organizational commitment does not have significant influence to stress management at work. The research results also uncover that interpersonal communication has significant influence to organizational commitment. In this matter, the influence depends on how close and urgent individual has to keep having relationships to some social groups/organizations. However, organizational commitment does not have significant influence to interpersonal communciation. As a life consequences in the information age, individual can select a kind of communication from traditional to electronic media as a way of maintaining self commitment to organization.